2019
DOI: 10.1002/adsc.201801547
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of (2H)‐Indazoles from Azobenzenes Using Paraformaldehyde as a One‐Carbon Synthon

Abstract: Rhodium(III)-catalyzed hydroxymethylation followed by intramolecular annulation of azobenzenes using paraformaldehyde as a valuable C1-feedstock is described. The method is readily extended to the coupling reaction between azobenzenes and trifluoroacetaldehyde. This transformation efficiently produces a range of C3-unsubstituted and C3-trifluoromethylated (2H)-indazoles, which are important targets in the development of novel bioactive compounds. Excellent chemoselectivity and functional group tolerance were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…According to above observations and previous reported studies, [ 14–22 ] a plausible catalytic cycle is proposed (Scheme 5). First, [RuCl 2 ( p ‐cymene)] 2 is converted by AgSbF 6 to the catalytically active ruthenium species I , which reacts with amide 1 to generate a five‐membered ruthenium intermediate II through chelate directed C–H activation.…”
Section: Figuresupporting
confidence: 58%
See 1 more Smart Citation
“…According to above observations and previous reported studies, [ 14–22 ] a plausible catalytic cycle is proposed (Scheme 5). First, [RuCl 2 ( p ‐cymene)] 2 is converted by AgSbF 6 to the catalytically active ruthenium species I , which reacts with amide 1 to generate a five‐membered ruthenium intermediate II through chelate directed C–H activation.…”
Section: Figuresupporting
confidence: 58%
“…Our study was intrigued by a previously reported procedure for the synthesis of 3‐unsubstituted phthalides from benzamides by Faigl, Volk and co‐workers, [ 13 ] involving ortho ‐lithiation, formylation, reduction and lactonization processes (Scheme 1c). Encouraged by the advances in the ortho ‐hydroxymethylation with paraformaldehyde via transition metal catalyzed C–H activation (e.g., ruthenium catalysis by Zhou, [ 14 ] Ding, [ 15 ] Wu, [ 16 ] and Kim [ 17 ] with pyridyl or pyrimidinyl as the directing group, rhodium catalysis by Kim [ 18 ] with azobenzene as substrate, manganese catalysis by Glorius [ 19 ] with pyridyl or pyrimidinyl as the directing group, cobalt‐catalyzed hydroxymethylarylation of terpenes with formaldehyde and arenes by Chen [ 20 ] ) and recent progress in the synthesis of 3‐substituted phthalides from benzamides and aldehydes by rhenium‐ [ 21 ] and rhodium‐catalysis, [ 22 ] we proposed that it might be possible to prepare 3‐unsubstituted phthalides in a single step by a sequential transition‐metal‐catalyzed ortho ‐hydroxymethylation and intramolecular lactonization strategy.…”
Section: Figurementioning
confidence: 99%
“…Kim and co-workers have reported the hydroxymethylation and subsequent intramolecular annulation reaction of azobenzenes with paraformaldehyde to afford 2H-indazole core (Scheme 45). [49] The reaction exhibited good functional group tolerance and excellent chemoselectivity. 2H-indazole formation was proceeded with hydroxymethylation of azobenzenes with formaldehyde by CÀ H bond functionalization followed by intramolecular cyclization and aromatization of ortho-hydroxy methylated azobenzene in the presence of [Cp*RhCl 2 ] 2 (2.5 mol%), AgSbF 6 (10 mol%), LiOAc (30 mol%) and Ag 2 CO 3 (30 mol%).…”
Section: Rh-catalyzed Synthesis Of Indazolesmentioning
confidence: 95%
“…Kim and co‐workers have reported the hydroxymethylation and subsequent intramolecular annulation reaction of azobenzenes with paraformaldehyde to afford 2 H ‐indazole core (Scheme ) . The reaction exhibited good functional group tolerance and excellent chemoselectivity.…”
Section: Rh‐catalyzed Synthesis Of Indazolesmentioning
confidence: 99%
“…This conversion efficiently afforded several C3-unsubstituted and C3-trifluoromethylated (2 H )-indazoles 43 and 45 , which are important molecules in organic chemistry and pharmaceutical sciences. The practicability of this approach is highlighted by its chemoselectivity, functional-group tolerance, and wide substrate scope [ 62 ].…”
Section: Different Synthesis Routes For the Construction Of Indazoles...mentioning
confidence: 99%